Comparative Transcriptome Reveals the Genes’ Adaption to Herkogamy of Lumnitzera littorea (Jack) Voigt - Zhang, Ying; Chen, Yukai; Zhou, Yan; Zhang, Jingwen; Bai, He; Zheng, Chunfang (Frontiers in Genetics, 2020)
Lumnitzera littorea (Jack) Voigt is among the most endangered mangrove species in China. The morphology and evolution of L. littorea flowers have received substantial attention for their crucial reproductive functions. However, little is known about the genomic regulation of flower development in L. littorea. De novo RNA sequencing was used to compare the transcriptome profiles of two kinds of L. littorea flowers, one type with a column embedded in the petals (L-1) that has a high correlation with aborted seeds and another herkogamy with a stretched flower style (L-2) during petal unfolding in flowering. A total of 138,857 transcripts were assembled into 82,833 unigenes with a mean length of 1055.48 bp. In addition, 82,834 and 34,997 unigenes were assigned to 52 gene ontology (GO) functional groups and 364 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, respectively. Compared with L-1, 1,874 DEGs were up-regulated and 2,393 DEGs were down-regulated in L-2. A total of 1,794 transcription factors (TFs) were identified with bHLH was the most abundant TF family, followed by B3, bZIP, MYB-related and NAC. Furthermore, 12 MADS-box genes, including 4 MIKC-type and 8 M-type TFs, were found to help out- pollination of L. littorea by herkogamy. The newly generated transcriptome and gene expression profiles provide valuable information about the genetic processes during L. littorea flowering, which should be useful for illuminating adaptive evolution relationships and understanding the endangered mechanism.